Analysis Of The Influence Of Transformational Leadership And Effective Communication On Organizational Performance And Effectiveness In The Organizational Development Process - Wicaksono, Arif; Salsabila, Raihana; Sumarna, Deddy; Miranda, Rezha; Hidayati, Tetra (International Journal of Economics, Business and Innovation Research, 2025)
Transformational leadership and effective communication are key elements in enhancing organizational performance. Transformational leaders inspire and empower employees by presenting a clear vision and offering individual attention, fostering collaboration and innovation. Effective communication reinforces this process by ensuring the transparent delivery of strategic visions and building synergy across individuals and divisions. Their integration enables organizations to adapt better to changing business environments, improve operational efficiency, and strengthen competitive advantage. Studies indicate that the synergy between transformational leadership and effective communication not only boosts employee engagement but also accelerates the implementation of organizational strategies. This approach helps create a work culture oriented towards innovation, collaboration, and sustainability, which collectively supports the achievement of both short-term and long-term objectives. This abstract highlight the importance of transformational leadership and effective communication as fundamental pillars in building a dynamic and competitive organization.